Application of high-speed cutting technology in automobile manufacturing. (August 2019) - Hao, Botao; Lin, Guomin
Abstract: High-speed cutting technology is widely used in stamping die, die-casting die and injection die for its high processing efficiency. Based on the characteristics and advantages of high-speed machining technology, this paper analyzes the application of high-speed machining technology in the manufacture of automobile parts, overlay parts, cylinder bodies and automobile wheels, taking the change of cutting speed and cutting temperature as the research object.